The Role of Digital Technology in the Transformation of Modern Accounting Practices - Nur Fadila Salju; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The architectural shifting of corporate disclosure mechanisms within digitalized global markets necessitates a profound re-engineering of routine transaction recording pipelines to sustain organizational survival. This investigation adopts a non empirical qualitative descriptive approach utilizing a rigorous systematic literature review design to examine the multi dimensional impact of digital technology adoption on contemporary financial frameworks. The analytical model relies on a multi layered qualitative synthesis technique to evaluate the underlying causal relationships between automated processing platforms, professional role adjustments, and internal control vulnerabilities. The findings indicate that while advanced cloud networks and robotic automation maximize processing efficiency, they actively force human practitioners to discard routine mechanical roles and assume high level advisory positions. Furthermore, the implementation of decentralized blockchain architectures and cognitive auditing tools embeds continuous anomaly tracking directly into governance frameworks, significantly reducing corporate fraud risks while simultaneously introducing system dependency variables. This study concludes that long term corporate resilience depends on the strategic alignment between advanced technological infrastructure and mature human resource capabilities.